Pushing Our Limits : Insights from Biosphere 2 - Nelson, Mark, 1947- (The University of Arizona Press, 2018)
Biospherian Mark Nelson offers insider perspectives on Biosphere 2 and bold insights into today's global ecological challenges--Provided by publisher.